Bacteriocin Typing of Serratia marcescens Isolates of Known Serotype/-Group - Traub, Walter H. (1972)
The number of isolates of Serratia marcescens that could be typed by sensitivity to bacteriocins was compared with the nature of the serotype/-group of each of the isolates. Ninety-four of 101 isolates (93.1%) could be bacteriocin-typed; this compares with 80 of the isolates (79.2%) that had been serotyped, and with 91 of the isolates (90.1%) that carried determinable O antigens. It is recommended that bacteriocin typing of S. marcescens be adopted by reference laboratories, because this technique is simple, inexpensive, and appears to be of somewhat higher epidemiological resolution than classic serological procedures.